Characterization of microencapsulated Saga Leaves Extract (Abrus precatorius L.) and Analgetic Activity Tests in Male Mice (Mus musculus) - Nabilah Nauli Jehan; Titik Sunarni; Dian Marlina (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Saga leaves are one of the plants that have analgesic activity. Saga leaves contain phenol compounds, flavonoids, tannins, alkaloids, and saponins. Phenol has instability with oxygen, light, and high temperatures. Therefore, the microencapsulation process is necessary. Microcapsule characterization in this study included encapsulation efficiency, particle size, distribution value and morphology. Objective: This research was to determine the characterization of microcapsules and the analgesic activity of saga leaf extract microcapsules in male mice. Methods: The microencapsulation process conducted in this study was carried out using the spray drying method. Saga leaf extract was coated with the coating material in the ratio of 1:20. Several ratios of maltodextrin (MD) and soy protein isolate (SPI) (100%:0%); (75%%:25); (50%:50%); (25%:75%) were applied as the coating material. The encapsulation efficiency was determined by comparing the total phenol content of the extract and microcapsule. Particle size and distribution values were tested using a particle size analyzer. Microcapsule morphology was seen using scanning electron microscopy. Analgesic activity test using the tail-flick method with mice as test animals. Data analysis in this study used one-way ANOVA. Results: The encapsulation efficiency obtained was 31.40-80.29%. The particle size obtained in the microcosm was 17.70-30.90 µm. The distribution value obtained was 1.42-2.45. The morphology of the microcapsule obtained was round and had wrinkles. The analgesic activity obtained in this study resulted in significantly different pain inhibition values before and after microencapsulation. Conclusion: The characteristics of microcapsule preparations are well-known, and the analgesic activity of various microcapsules was 42.43-57.15%.